Design and health: an interdisciplinary baseline experience of product design for health needs of the Chilean elderly - Juan Carlos Briede Westermeyer; Cristhian Perez Villalobos; Pablo Olivera Morales; Rocio Glaria Lopez; Carolina Bustamanete Duran (Journal of the Pakistan Medical Association, 2020)
Abstract Objective: Describing the results of a User-Centered Design workshop using Challenge Based Learning or CBL, where students from Chilean industrial design and health degrees, developed solutions to resolve health problems among the elderly. Method: It was a pre-experimental study; 45 university students took part in a workshop: 39 from Industrial Design, 3 from Speech Therapy, 2 from Medical Technology and 1 from Medicine. In this workshop, the students, using CBL in disciplinary heterogeneous groups, faced a 3-week challenge to develop products to overcome a health problem for an elderly person. Once the product was presented, the professors and students assessed the conceptual proposals, using a semantic differential. The students also evaluated the workshop with a perception survey. Results: Both the students and professors positively evaluated the usefulness and functionality of the conceptual proposals; although, the industrial design students were more critical about these aspects. The originality of proposals evaluated was the worst. Regarding the workshop, all students (100%) felt that instructions were clear as were the three moments of design, with problem definition stage best evaluated. Conclusions: The CBL is shown to be an educational tool that allows training professionals in product design and in developing health technology that is suitable for the users' needs. Regarding the process, heterogeneous make-up of the groups and clear external guide appear as essential for CBL to work well. Keywords: challenge-based learning, elderly, interdisciplinary, higher education. Continuous...